Empirical study of factors affecting college students' problematic smartphone usage during the global pandemic - Zadrian Ardi; Chiedu Eseadi; Mkpoikanke Sunday Otu; Hendra Hidayat (Universitas Negeri Padang, 2022)
The increase in the frequency, duration and dependence of individuals using smartphones in the last decade has resulted in a phenomenon of mental health disorders in the form of problematic smartphone usage. This study aims to analyze the causes of problematic smartphone usage based on the conditions of Fear of Missing Out (FOMO), loneliness, virtual presence, and future time perspectives.This study uses a quantitative approach through survey methods and uses a cross-sectional study method and post-positivism assumptions to look at the factors that cause dependent variables. In this study, 597 students were involved, with 290 males (48.57%) and 307 females (51.43%). Path analysis was used in the analysis of this study to determine the impact of the direct and indirect effects of exogenous variables on endogenous variables. Path analysis is also used in mapping and testing the hypotheses that make up the model. The study results show that the virtual presence, loneliness, and future time perspective variables impact individuals' emergence of FOMO conditions, which in turn contributes to the formation of problematic smartphone usage. The study of the direct and indirect relationships of the variables is discussed.